Multicenter survey on the use of device-assisted enteroscopy in Portugal - Pinho, Rolando (2016)
Background: Device-assisted enteroscopies (DAEs) are recent endoscopic techniques that enable direct endoscopic smallbowel evaluation. Objective: The objective of this article is to evaluate the implementation of DAEs in Portugal and assess the main indications, diagnoses, diagnostic yield, therapeutic yield and complication rate. Methods: We conducted a multicenter retrospective series using a national Web-based survey on behalf of the Portuguese Small-Bowel Study Group. Participants were asked to fill out two online databases regarding procedural data, indications, diagnoses, endoscopic therapy and complications using prospectively collected institutional data records. Results: A total of eight centers were enrolled in the survey, corresponding to 1411 DAEs. The most frequent indications were obscure gastrointestinal bleeding (OGIB), inflammatory bowel disease and small-bowel tumors. The pooled diagnostic yield was 63%. A relation between the diagnostic yield and the indications was clear, with a diagnostic yield for OGIB of 69% (p ¼ 0.02) with a 52% therapeutic yield. Complications occurred in 1.2%, with a major complication rate of 0.57%. Perforations occurred in four patients (0.28%). Conclusion: DAEs are safe and effective procedures, with complication rates of 1.2%, the most serious of which is perforation. Most procedures are performed in the setting of OGIB. Diagnostic and therapeutic yields are dependent on the indication, hence appropriate patient selection is crucial.